A combination of high dose rate (10X FFF/2400 MU/min/10 MV X-rays) and total low dose (0.5 Gy) induces a higher rate of apoptosis in melanoma cells in vitro and superior preservation of normal melanocytes. Issue 5 (October 2015) - Sarojini, Sreeja; Pecora, Andrew; Milinovikj, Natasha; Barbiere, Joseph; Gupta, Saakshi; Hussain, Zeenathual M.; Tuna, Mehmet; Jiang, Jennifer; Adrianzen, Laura; Jun, Jaewook; Catello, Laurice; Sanchez, Diana; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to determine the apoptotic effects, toxicity, and radiosensitization of total low dose irradiation delivered at a high dose rate in vitro to melanoma cells, normal human epidermal melanocytes (HEM), or normal human dermal fibroblasts (HDF) and to study the effect of mitochondrial inhibition in combination with radiation to enhance apoptosis in melanoma cells. Cells irradiated using 10X flattening filter-free (FFF) 10 MV X-rays at a dose rate of 400 or 2400 MU/min and a total dose of 0.25–8 Gy were analyzed by cell/colony counting, MitoTracker, MTT, and DNA-damage assays, as well as by quantitative real-time reverse transcriptase PCR in the presence or absence of mitochondrial respiration inhibitors. A dose rate of 2400 MU/min killed on average five-fold more melanoma cells than a dose rate 400 MU/min at a total dose of 0.5 Gy and preserved 80% survival of HEM and 90% survival of HDF. Increased apoptosis at the 2400 MU/min dose rate is mediated by greater DNA damage, reduced cell proliferation, upregulation of apoptotic genes, and downregulation of cell cycle genes. HEM and HDF were relatively unharmed at 2400 MU/min. Radiation induced upregulation of mitochondrial respiration in both normal and cancer cells, and blocking the respiration with inhibitors enhanced apoptosis only in melanoma cells. A high dose rate with a low total dose (2400 MU/min, 0.5 Gy/10X FFF 10 MV X-rays) enhances radiosensitivity of melanoma cells while reducing radiotoxicity toward HEM and HDF. Selective cytotoxicity of melanoma cells is increased by blocking mitochondrial respiration.